Patient perspectives on the Tailored intervention for Anxiety and Depression Management in COPD (TANDEM): a qualitative evaluation - Ratna Sohanpal; Kristie-Marie Mammoliti; Amy Barradell; Moira Kelly; Sian Newton; Liz Steed; Vari Wileman; Vickie Rowland; Clarisse Dibao-Dina; Anna Moore; Hilary Pinnock; Stephanie J. C. Taylor (BMC, 2024)
Abstract Background Chronic obstructive pulmonary disease (COPD) is commonly associated with anxiety/depression which can affect self-management and quality of life. The TANDEM trial evaluated a cognitive behavioural approach intervention targeting COPD-related symptoms of anxiety and/or depression, comprising up to eight one-to-one sessions delivered by respiratory healthcare professionals prior to pulmonary rehabilitation (PR). The intervention showed no improvement in anxiety/depression or uptake/completion of PR. We present patient perspectives of the intervention to help understand these results. Method Semi-structured individual interviews, using a semi-structured topic guide informed by Sekhon's Theoretical Framework of Acceptability, were conducted with 19 patients between September 2019 and April 2020. The interviews were audio-recorded, transcribed verbatim and analysed thematically. Results The following could have limited the impact of the intervention: (1) The lives of patients were complex and commonly affected by competing comorbidities or other external stressors which they managed through previously adopted long-standing coping strategies. (2) Some patients were reluctant to talk about their mood despite the Facilitators' training and person centred-skills which aimed to enable patients to talk freely about mood. (3) The intervention handouts and 'home-practice' were perceived as helpful for some, but not suitable for all. (4) Many patients perceived improvements in their physical and mental health, but this was not sustained due to a mix of personal and external factors, and some did not perceive any benefits. (5) PR non-attendance/non-completion was a result of personal and PR service-related reasons. (6) Discussing COPD and mental health with the Facilitator was a novel experience. Many patients felt that TANDEM could be of benefit if it was offered earlier on/at different time points in the COPD illness journey. Conclusion We found the delivery of TANDEM prior to PR was not helpful for patients with advanced COPD often experiencing other comorbidities, and/or difficult personal/external events. These patients already utilised long-standing coping strategies to manage their COPD. Holistic interventions, that address the impact of COPD in relation to wider aspects of a patients' life, may be more beneficial. Trial registration ISRCTN Registry 59,537,391. Registration date 20 March 2017.